Risk reduction in dominant temporal lobe epilepsy surgery combining fMRI/DTI maps, neuronavigation and intraoperative 1.5-Tesla MRI - Roessler, Karl; Sommer, Bjoern; Grummich, Peter; Hamer, Hajo; Pauli, Elisabeth; Coras, Roland; Blümcke, Ingmar; Buchfelder, Michael (Stereotactic and Functional Neurosurgery, 2015)
In dominant temporal lobe epilepsy surgery, speech, memory and visual systems are at risk.Functional magnetic resonance imaging (fMRI) and diffusion tensor imaging combined with intraoperative neuronavigation and MRI were investigated retrospectively regarding risk reductions for favorable neurological and seizure outcome.Functional imaging risk maps were generated for 14 patients suffering from dominant temporal lobe epilepsy [7 with hippocampal sclerosis (HS), 7 with various lesions] and used for neuronavigation-guided tailored resection. Postoperative neurological and seizure outcome and complications were evaluated.None of the patients had postoperative speech dysfunction despite 2.3/3.6-cm mean hippocampal/neocortical resection. Verbal memory decline was found in 2 of the 14 (14.3%) patients, correlating with surgical lesions in fMRI memory-activated functional areas in the dominant posterior parahippocampal gyrus. Verbal memory scores did not statistically differ between the HS and the lesional group, neither pre- nor postoperatively. A contralateral visual field defect occurred in 1 patient (7.1%). An Engel class I seizure outcome was found in 12 patients (85.7%), and 11 were completely seizure free (78.6%) at a mean follow-up of 19.5 months.This retrospectively investigated protocol led to an excellent neurological and seizure outcome and a low complication rate in dominant temporal lobe epilepsy surgery.
EVALuna2:7287